Elaboración de un Protocolo y Metodología de recolección de especies de Hongos en la estructura del Sustrato Vegetal del Bosque Siempre Verde Pie Montano (bspn01) de la Cordillera Occidental de Los Andes en el Recinto Los Laureles entre el Cantón Pangua y La Maná en el período 2019 – 2020. - Maldonado Campaña, Yajaira Elizabeth (2020)
This research is carried out based on the analysis of bibliographic information of articles made in different sectors that contain characteristics similar to the study area. The objective was to develop a protocol and methodology for the collection of fungal species in the structure of the plant substrate the study was carried out in the Western Cordillera of the Andes in the Evergreen Pie Montano forest that is located in the Los Laureles enclosure between the Pangua canton and La Maná. An inductive and deductive methodology was carried out that goes from the particular to the general of a descriptive type. In the methodological process, the theoretical reference of the authors Pfenning and Magalhães, 2012 was found who affirm that, “The methodology to isolate and control fungi from complex ecosystems such as the soil shows inherent limitations due to the natures of the species and the inability of the culture media to accurately copy soil habitats”. The study area was identified using the GIS software. A protocol for collecting soil fungi species such as saprophytes and plant pathogens was designed in the structure of the plant substrate for the cultivation of fungi in the field and in the laboratory. In conclusion, with the selection of techniques and adequate methodology, bearing in mind the geomorphology, edaphic, meteorological, geological and hydrogeological conditions of the area, it was possible to isolate and characterize the fungi belonging to the group of microorganisms that affect the plant substrate.